Effect of different biostimulation methods on endocrinological profiles of mithun bulls - PERUMAL, P (The Indian Journal of Animal Sciences, 2018)
A study was conducted to assess the effect of biostimulation methods on endocrinological profiles of mithun bulls. Adult male (6, 4–5 year old) with good body condition score (5–6) from herd of mithun farm of the institute were selected for the present study. The biostimulation methods were grouped into 9 groups and each group consisted of 6 animals, viz. Gr 1 (without exposure of female), Gr 2 (exposure of urine of non-estrus female), Gr 3 (exposure of urine of estrus female), Gr 4 (exposure of dung of non-estrus female), Gr 5 (exposure of dung of estrus female), Gr 6 (exposure of sweat of non-estrus female), Gr 7 (exposure of sweat of estrus female), Gr 8 (exposure of nonestrus female) and Gr 9 (exposure of estrus female). Exposure to each group was done with the interval of 1 month. The experiment was replicated 3 times. Blood samples were collected 15 min after exposure to the different methods of biostimulation for estimation of testosterone, thyroxine (T4) and cortisol, and at 30 min for follicle stimulating hormone (FSH) and luteinizing hormone (LH). Hormone profiles revealed a significant difference among the different methods of biostimulation in mithun bulls. The hormone profiles were significantly higher in adult mithun bulls that were exposed to estrus female followed by exposed to urine, dung, sweat of estrus female and lowest was observed in secretions of non-estrus animal groups. Through this investigation, a suitable model was developed to improve the endocrinological profiles by use of biostimulation techniques in mithun bulls which inturn will indirectly support will to higher semen production and its quality for artificial breeding programme.